Memorandoms by James Martin : An Astonishing Escape from Early New South Wales - Martin, James (Book collections on Project MUSE., 2017)
Among the vast body of manuscripts written and collected by the philosopher and reformer Jeremy Bentham (1748-1832), held by UCL Library's Special Collections, is one of the most important documents in the histories of European Australia and of convict transportation. The Memorandoms of James Martin is the only known narrative written by members of the first cohort of prisoners transported to Australia, is the first Australian convict narrative, and is the only first-hand account of the best-known Australian convict escape. On the night of 28 March 1791, James Martin, William Bryant, his wife.